Locally nilpotent groups of finite non-Abelian sectional rank - Dashkova, O. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We introduce the notion of non-Abelian sectional rank of a group and study locally nilpotent non-Abelian groups of finite non-Abelian sectional rank. It is proved that the (special) rank of these groups is finite.